2011
DOI: 10.1007/s11010-011-1038-4
|View full text |Cite
|
Sign up to set email alerts
|

Effect of sydnone SYD-1 on certain functions of LPS-stimulated macrophages

Abstract: In an earlier article, we demonstrated that sydnone SYD-1 (3-[4-chloro-3-nitrophenyl]-1,2,3-oxadiazolium-5-olate) inhibits electron transport in the respiratory chain and uncouples oxidative phosphorylation, and postulated that these effects are probably involved in its antitumor activity. We now report the effect of SYD-1 on certain macrophage functions, considering the important role of these cells in inflammatory response and also the relevant anti-inflammatory activity reported for some sydnones. Incubatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Among the push–pull organic systems known, the mesoionic compounds (MICs) deserve special attention because of their remarkable physical and chemical properties that enable applications as antioxidant, anti-inflammatory, antibacterial, and antitumor sumstances, as well as the large NL optical susceptibility as already proposed and experimentally demonstrated. Indeed, the MICs’ properties point to NL biophotonics as a possible avenue for future applications.…”
Section: Introductionmentioning
confidence: 99%
“…Among the push–pull organic systems known, the mesoionic compounds (MICs) deserve special attention because of their remarkable physical and chemical properties that enable applications as antioxidant, anti-inflammatory, antibacterial, and antitumor sumstances, as well as the large NL optical susceptibility as already proposed and experimentally demonstrated. Indeed, the MICs’ properties point to NL biophotonics as a possible avenue for future applications.…”
Section: Introductionmentioning
confidence: 99%
“…The mesoionic compound Syd‐1 (fig. A ) was synthesized in the Department of Chemistry, Federal Rural University of Rio de Janeiro. N ‐(4‐chloro‐3‐nitrophenyl)‐sydnone.…”
Section: Methodsmentioning
confidence: 99%
“…Of the mesoionic compounds, 1,2,3‐oxadiazole‐5‐olates, also called sydnones, have been the most extensively studied . Sydnones have numerous pharmacological activities, including antibacterial, anti‐inflammatory, analgesic and antitumour effects . In addition to the pharmacological activities that have been attributed to these compounds, sydnones also have great importance because they act as precursors of bioactive molecules .…”
mentioning
confidence: 99%
“…Studies proved that PLA2 inhibitors can be as potent as steroidal anti-inflammatory drugs due to the reduction of lipid mediators which were usually secreted as a response to tissue injury [56]. Others found that 3-(4-chloro-3-nitro) sydnone mimicked the anti-inflammatory and immunosuppressive agents by reducing phagocytic activity, increasing superoxide anion production, inhibiting the production of nitric oxide, and declining interleukin-6 (IL-6) levels in peritoneal macrophages [57].…”
Section: Anti-inflammatory Activitymentioning
confidence: 99%